THE TRASH BECOMES PROFIT FOR BRAZILIAN GROCERY RETAIL - Braga Junior, Sergio Silva [UNESP]; Silveira Dias, Karina Tonelli [UNESP]; Oliveira Braga, Waleska Reali de [UNESP]; Forti, Juliane Cristina [UNESP] (Univ Autonoma Caribe-uac, 2019)
Environmental sensitivity is present in several countries, and in Germany and the Netherlands, this perception on the part of agents (companies and individuals) is quite high. In this context, retailers have begun to take on new tasks, such as the commitment to reduce the waste they generate and to recycle and reuse what is generated with the purpose of increasing their responsibility to the final consumer. Therefore, the aim of this work was to analyze the reverse logistics implemented in 22 grocery stores located in Sao Paulo (Brazil) and to quantify the profit obtained with this implementation. For this, for 24 months, the quantities of cardboard and plastic discarded by these grocery stores were monitored. As a result, it was possible to observe that the supermarket corporation increased its net profit with the practice of reverse logistics in a value proportional to the net profit generated by two supermarkets with a revenue of 600 thousand dollars.
Keywords: Reverse Logistics; Grocery Retail; Supermarket; Sustainability; Waste Management